Tubuh Sosial Siswi Madura: Studi Kasus Di SMPN 1 Labang - Naufalul Ihyaâ€™ Ulumuddin; Akbar Mawlana (Universitas Merdeka Madiun, 2021)
Abstractâ€” Education and the body are closely related. School as a means of education does not only transfer knowledge to students, but also hones awareness of their bodies. However, in the field, it shows that Madurese female students who study in Madura do not realize that their bodies are the objects of power relations that operate through a hidden curriculum. This research tries to explain the cause. In order to obtain data about it, a case study approach, as a cluster of qualitative methods, was used in this field work. The data, which were mostly obtained from unstructured interviews, were then explained using social body studies. The results of this study indicate that the body as an object of power relations appears in the regulation of the use of the headscarf (â€œJilbabâ€)for Madurese female students, especially those who attend SMPN 1 Labang, Bangkalan. Thus, the public schools there seem to discipline Madurese female students as if they are undergoing a regular Islamic boarding school or madrasah education almost everyday life. Keywordsâ€”: Social Body Studies; Education; MadureseFemale Students.